2003
DOI: 10.1038/nrm1202
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and regulation of human non-homologous DNA end-joining

Abstract: Non-homologous DNA end-joining (NHEJ)--the main pathway for repairing double-stranded DNA breaks--functions throughout the cell cycle to repair such lesions. Defects in NHEJ result in marked sensitivity to ionizing radiation and ablation of lymphocytes, which rely on NHEJ to complete the rearrangement of antigen-receptor genes. NHEJ is typically imprecise, a characteristic that is useful for immune diversification in lymphocytes, but which might also contribute to some of the genetic changes that underlie canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
662
1
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 875 publications
(680 citation statements)
references
References 93 publications
8
662
1
9
Order By: Relevance
“…It was thought that because hairpins are not generated in CSR, Artemis does not play a role in this process 24. Therefore the role of the DNA–PK complex in CSR was considered to be in regulating end processing, possibly by phosphorylating other proteins 25. However, it has since been shown that Artemis is indeed involved in CSR, where its nuclease activity may function in resolving more complex lesions that are generated during CSR 26.…”
Section: Mechanisms Of Recombination In Lymphoid Cellsmentioning
confidence: 99%
“…It was thought that because hairpins are not generated in CSR, Artemis does not play a role in this process 24. Therefore the role of the DNA–PK complex in CSR was considered to be in regulating end processing, possibly by phosphorylating other proteins 25. However, it has since been shown that Artemis is indeed involved in CSR, where its nuclease activity may function in resolving more complex lesions that are generated during CSR 26.…”
Section: Mechanisms Of Recombination In Lymphoid Cellsmentioning
confidence: 99%
“…(6,7) RAG-1 and RAG-2 proteins act in concert to assemble an appropriate pair of RSSs into a synaptic complex and introduce double-strand breaks (DSBs). (16)(17)(18)(19)(20)(21)(22)(23) The induced DSBs are then repaired by nonhomologous DNA end joining with addition or deletion of nucleotides. (19,24) Recent studies have shown that the LMO-2, Ttg1, Tal1(SCL1), Tal2 (SIL), MTS1 fragile sites represent unintended or cryptic sites (pseudo-signals is another term for these), which the RAGs treat as normal RSS sequences because their sequence is quite close to that of an RSS.…”
Section: Lymphoid Translocations: An Overviewmentioning
confidence: 99%
“…(16)(17)(18)(19)(20)(21)(22)(23) The induced DSBs are then repaired by nonhomologous DNA end joining with addition or deletion of nucleotides. (19,24) Recent studies have shown that the LMO-2, Ttg1, Tal1(SCL1), Tal2 (SIL), MTS1 fragile sites represent unintended or cryptic sites (pseudo-signals is another term for these), which the RAGs treat as normal RSS sequences because their sequence is quite close to that of an RSS. (25)(26)(27)(28) This misrecognition of the target sequence leads to these translocations or deletions.…”
Section: Lymphoid Translocations: An Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to HR, NHEJ is an error-prone DSB repair mechanism, that involves the DNA-dependent protein kinase (DNA-PK) and the DNA ligase IV (Lig4) complex, which together facilitate re-joining of broken non-compatible DNA ends (Lieber et al, 2003). The DNA-PK complex contains Ku70 and Ku80 proteins, which recognize the break and mediate recruitment of the DNA-PK catalytic subunit, a protein kinase required for efficient NHEJ (Lees-Miller and Meek, 2003;Bassing and Alt, 2004;Burma and Chen, 2004).…”
Section: Introductionmentioning
confidence: 99%